TINJAUAN YURIDIS TERHADAP PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR DALAM SISTEM PEMERINTAHAN DAERAH DI INDONESIA - susilawan, muhammad andi; ikhsan, ikhsan; haryono, dodi (Lampung University, 2014)
Election of Governor and Deputy Governor in Law Number 32 of 2004 which is elected directly by the people. From the results of this study concluded that there are several principles. First, the background is applied to the election of the governor and vice governor directly in Law Number 32 of 2004 on Regional Government, philosophically motivated to carry out direct elections is partly due to indirect mechanisms of democracy does not guarantee accommodation in choosing future leaders. Second, the strengths and weaknesses of the election for governor and vice governor directly in Law Number 32 of 2004 on Regional Government, the benefits are local elections in person an opportunity for political education, the system of checks and balances between the legislative and executive more balanced, as a means to strengthen regional autonomy. As for the cost of the funds needed in the election for governor and lieutenant governor are relatively higher, opening the possibility of conflict and elite, activities of people with disabilities, especially during the campaign. Thirdly, it is necessary to correct weaknesses gubernatorial election in accordance with the development of local government is currently increasing citizens political awareness, empowerment of the governor and deputy governor are direct, general, free, confidential, honest, and fair. election of governors and vice-governors enforcement of financial restrictions consistent and campaigns.Keywords: Election of Governor and Deputy Governor, Local Government